Effect of Electroacupuncture on Chondrocyte Apoptosis and Cartilage Matrix of Experimental Rats with Knee Osteoarthritis - Guangwen WU; Chunsong ZHENG; Xihai LI; Qiuying LIN; Yichen DAI; Qiuxiang LIN; Yuanyuan ZHANG; Mingxia WU (康复学报)
Objective:To observe the effect of electroacupuncture on chondrocyte apoptosis and cartilage matrix of rats with knee osteoarthritis (KOA), so as to explore its treatment mechanism on knee osteoarthritis.Methods:After one week of acclimation, 40 clean, two-month-old male Sprague Dawley (SD) rats were randomly divided into blank group (n=10) and model group (n=30). The knee osteoarthritis rat model was induced by injecting 0.2 mL 4%papain solution on days 1, 4 and 7. After the model were successfully established, the induced knee osteoarthritis rats were randomly divided into three groups: the model group (without any treatment, n=10), the EA 15 min group (received electroacupuncture treatment for 15 min/once/day, 5 times/week, n=10) and the EA 30 min group (received electroacupuncture treatment for 30 min/once/day, 5 times/week, n=10). The blank group did not receive any treatment. After 8 weeks, the rats were sacrificed and blood from the abdominal aorta was obtained, and then measured the C-terminal peptide of collagenⅡ(CTXⅡ) and collagenⅡC-propeptide (CPⅡ) by ELISA. The medial cartilages of right tibial plateau were obtained, and fixed in 4%paraformaldehyde, and embedded in paraffin. TUNEL was performed to assess the chondrocyte apoptosis. Toluidine blue stain and collagenⅡimmunohistochemistry stain was performed to assess the contents of proteoglycan and collagenⅡ, respectively. The cartilages of left tibial plateau were obtained, and saved in liquid nitrogen, and then measured the mRNA and protein levels of Bcl-2 and Bax by RT-PCR and Western blot, respectively.Results:Compared with the blank group, the chondrocyte apoptosis rate in the model group was significantly increased (P<0.05); the mRNA and protein expression of Bcl-2 was decreased (P<0.05), and the mRNA and protein expression of Bax was significantly increased (P<0.05). Toluidine blue stain indicated that there was proteoglycan loss in the model group. CollagenⅡimmunohistochemistry stain indicated that there was collagenⅡloss in the model group (P<0.05). CTXⅡin serum was significantly increased (P<0.05), and CPⅡin serum was significantly decreased in the model group (P<0.05). Compared with the model group, the electroacupuncture treatment group can significantly reduce the chondrocyte apoptosis rate (P<0.05);promote the mRNA and protein expression of Bcl-2(P<0.05);reduce the mRNA and protein expression of Bax (P<0.05);increase proteoglycan and typeⅡcollagen content (P<0.05);reduce levels of CTXⅡand raise CPⅡ(P<0.05).Conclusion:Electroacupuncture can delay cartilage degeneration by effectively reducing chondrocyte apoptosis and articular matrix destruction of rats with knee osteoarthritis, this may explain its clinical efficacy in the treatment of KOA.